Index-aware Model Order Reduction Methods Applications to Differential-Algebraic Equations - Banagaaya, N.; Alì, Giuseppe; Schilders, Wil H.A.; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2016)
The main aim of this book is to discuss model order reduction (MOR) methods for differential-algebraic equations (DAEs) with linear coefficients that make use of splitting techniques before applying model order reduction. The splitting produces a system of ordinary differential equations (ODE) and a system of algebraic equations, which are then reduced separately. For the reduction of the ODE system, conventional MOR methods can be used, whereas for the reduction of the algebraic systems new methods are discussed. The discussion focuses on the index-aware model order reduction method (IMOR) and its variations, methods for which the so-called index of the original model is automatically preserved after reduction.
Introduction -- Diﬀerential-Algebraic Equations -- Decoupling of linear constant DAEs -- Index-aware model order reduction -- Large scale problems -- Conclusion.
Keywords: Mathematics -- Data processing; Electrical engineering; Computer science -- Mathematics; Computational Mathematics and Numerical Analysis; Electrical and Electronic Engineering; Mathematics of Computing